PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK SISWA KELAS V SD NEGERI 6 KADUR - Zulhendri Zulhendri; Otang Kurniaman; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the fact that the students' learning achievement is low and there are still many students who have not reached the minimum completeness criteria that has been set. From 23 students only 10 students (43,7%) reaching minimum completeness criteria. And 13 students did not reach KKM (56,52%).This research is a classroom action research conducted on Grade V Students of SDN 6 Kadur Rupat Utara. The Research Instrument consists of Learning Devices used in this study based on Education Unit Level Curriculum (KTSP) or known as Curriculum 2006. Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The first meeting of the first cycle of teacher activity is the average activity of teachers observed in cycle II has increased compared to cycle I. At the first meeting of the cycle I average teacher activity 60.71% in the category enough, the average teacher activity increased to 78.57% in the Good category.At the third meeting of cycle II, the average of 82.14% of the teacher activity was very good and at the fourth meeting with the average activity 89.25% in the Very Good category. The first meeting of the first cycle of student activity average 75% with sufficient category, at the second meeting the average activity increased to 82.14% with good category.In the third meeting of cycle II the average student activity 89.25% in very good category and at the fourth meeting increased compared to the previous meeting with an average of 96.42% student activity with very good category. Student learning outcomes after preliminary student data above minimum completeness criter only 10 people (43.47%) after cycle I increased up to 16 people (9,13%) after the second cycle increased more until reaching 22 people (14,59% ). Similarly, the average value obtained by students in the classical at the initial data is only 17.4 and after the first cycle increased by an average of 69.6 and in the second cycle increased by 95.65. This means that the classic value obtained by students has been above the minimum completeness criteriathat has been set.Keywords: Inquiry Learning Model, Learning Result Indonesian